A United Europe of Things
XIII, 135 p. 1 illus.
Keywords: This volume studies high and late medieval material culture in a Pan-European context. The idea of ‘unity of culture’ in Medieval Latin Europe is well known in historical texts, especially when it concerns the so-called ‘Europe North of the Alps’. This book investigates the similarities and differences in material culture between areas, regions and political entities and opens the dialogue for a more interregional discussion. The editors acknowledge that there are numerous challenges in understanding the phenomenon the volume addresses, the fundamental one being defining (or even redefining) a common material culture of Europe. Important in determining this is greater appreciation of how objects reflect interactions between peoples, both local and foreign, which can be driven by a variety of factors, including trade, conflict and diplomacy etc. But just as important is observing the differences between ‘things’ across Europe, reflecting developments and transformations its cultural, social and economic history. These works are traditionally presented in isolation or at the local level, maybe even in very specialized tomes, as often it is thought their observation are not relevant to wider discourses. Conversely, what is clear, however, is that by interconnecting these seemingly introvert studies of specific artefact types or sites etc., readers can better appreciate the similarities and differences in material culture across Europe. This book is of interest to researchers in archaeology and material culture.